Wages and productivity in Argentinian manufacturing: A structuralist and distributional firm-level analysis - María Celeste Gómez; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
Wages and productivity represent two of the most relevant variables to consider in economic development. Given the low productivity levels that emerging countries reveal, the accumulation of productive capabilities and a narrower dispersion across sectors would enable emerging countries to overcome the middle-income trap. Y et, this positive trend in productivity should translate into higher wages. Thus, we pose the following questions applied to a middle-income trapped country: is there a link between labour productivity and wages in the Argentine manufacturing sector? Does it differ across techno-productive classes or wage levels? Which factors affect this nexus, considering premature deindustrialisation? Using a firm-level dataset from 2010 to 2016, we perform quantile regression estimates to evaluate the link between productivity and wages across the conditional wage distribution among manufacturing firms. Based on a structural analysis, we identify the differences in these elasticities at 2-ISIC code levels and across Pavitt taxonomies. Our results confirm a positive , but extremely low, pass-through between productivity and wages in the Argentinian manufacturing firms, different across sectors according to their techno-productive capabilities, robust under different empirical strategies.
Keywords: J31; D24; L6; O14; C21; 330; Gains from productivity; Development; Asymmetries